Wnt signals across the plasma membrane to activate the beta-catenin pathway by forming oligomers containing its receptors, Frizzled and LRP. - Cong, F.; Schweizer, L.; Varmus, H. (Development, 2004)
Wnt-induced signaling via beta-catenin plays crucial roles in animal development and tumorigenesis. Both a seven-transmembrane protein in the Frizzled family and a single transmembrane protein in the LRP family (LDL-receptor-related protein 5/6 or Arrow) are essential for efficiently transducing a signal from Wnt, an extracellular ligand, to an intracellular pathway that stabilizes beta-catenin by interfering with its rate of destruction. However, the molecular mechanism by which these two types of membrane receptors synergize to transmit the Wnt signal is not known. We have used mutant and chimeric forms of Frizzled, LRP and Wnt proteins, small inhibitory RNAs, and assays for beta-catenin-mediated signaling and protein localization in Drosophila S2 cells and mammalian 293 cells to study transmission of a Wnt signal across the plasma membrane. Our findings are consistent with a mechanism by which Wnt protein binds to the extracellular domains of both LRP and Frizzled receptors, forming membrane-associated hetero-oligomers that interact with both Disheveled (via the intracellular portions of Frizzled) and Axin (via the intracellular domain of LRP). This model takes into account several observations reported here: the identification of intracellular residues of Frizzled required for beta-catenin signaling and for recruitment of Dvl to the plasma membrane; evidence that Wnt3A binds to the ectodomains of LRP and Frizzled; and demonstrations that a requirement for Wnt ligand can be abrogated by chimeric receptors that allow formation of Frizzled-LRP hetero-oligomers. In addition, the beta-catenin signaling mediated by ectopic expression of LRP is not dependent on Disheveled or Wnt, but can also be augmented by oligomerization of LRP receptors.